СУТЬ ТА ОСОБЛИВОСТІ ФОРМУВАННЯ ОСОБИСТОСТІ У КОНЦЕПЦІЇ ХРИСТИЯНСЬКИХ ДУХОВНО-МОРАЛЬНИХ ЦІННОСТЕЙ - Гелета, Олена (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті розглядаються суть і особливості формування особистості у концепції християнських духовно-моральних цінностей; розкрито сутність, мету, завдання та особливості формування духовного світу дитини; розроблено морально-ціннісну парадигму формування дитячого мислення та концепцію, що ґрунтується на культуровідповідності, яка передбачає органічну єдність формування духовності з історією і культурою народу, його мовою, звичаями, традиціями; визначили принципи релігійно-морального виховання. В статье рассматриваются сущность и особенности формирования личности в концепции христианских духовно-нравственных ценностей; раскрыта сущность, цели, задачи и особенности формирования духовного мира ребенка; разработаны нравственно-ценностную парадигму формирования детского мышления и концепции, основанной на культурном соответствии, которая предусматривает органическое единство формирования духовности с историей и культурой народа, его языком, обычаями, традициями; определили принципы религиозно-нравственного воспитания. The article deals with the essence and peculiar properties of personality formation in the concept of Christian spiritual and moral values. It states the purpose, task and peculiar features of a child’s spiritual world formation. It determines the principles of religious and moral education. The author presents the paradigm of moral values for child’s mind formation together with the concept of cultural compliance, which presumes the organic unity of spiritual development and the culture, history, language and traditions of a nation. Religious and moral education is a purposeful process that combines different means of religious and moral control over a child’s education which is aimed at training and educating a spiritual person with a good knowledge of their rights, obligations, and responsibility for their actions. Nowadays religious and moral education is very important as it is inclined: 1) to educate a person that seeks self-perfection and the likeness of God; 2) to educate a person who knows that their soul will be responsible before God for all their good and bad deeds; 3) educate the person that is willing to follow Christian norms of behavior.